Abstracts and guest editorial from the HFESNZ Conference 2025 - Green, Nicola (New Zealand Journal of Health and Safety Practice, 2025)
On October 2nd and 3rd 2025 Human Factors and Ergonomics Society of New Zealand (HFESNZ) held its 2025 conference at the George in Ōtautahi Christchurch. Human factors and ergonomics (HFE) is concerned with understanding the interactions between people and the things around them and applying this to design systems for optimal well-being and performance. HFE is multi-disciplinary, and principles are applied across tasks, jobs, products, environments, and industries which makes for interesting and stimulating conference conversations. The 2-day conference followed the HFESNZ hosted HFE in Healthcare Symposium on October 1. To align these events, the first day of the conference began with a healthcare-focussed session with Professor Paul Bowie, our guest from NHS Scotland, giving a keynote presentation. Paul’s expertise spans patient safety science, medical education and HFE and his address linked these domains providing excellent insights for us in Aotearoa as we work to embed an HFE approach in healthcare. Arranged by industry themes, other sessions included forestry, work-related musculoskeletal disorders and transport related topics. The conference theme of Bouncing Back-Leaping Forward helped participants to reflect on the strong base of HFE while thinking about what we can offer in contemporary and future work. This was highlighted in the keynote address given by Professor Rob Lindemann (University of Canterbury) who discussed virtual reality, its applications and potential pitfalls and followed up by a series of presentations on Artificial Intelligence. The conference was rounded out by a ‘workplace’ session covering neurodivergence, working from home, SME health and safety and team effectiveness. An important part of any HFESNZ conference is time and space to connect with people and discuss cross-industry and cross-specialism alignments and experiences to grow HFE knowledge, spark collaboration and innovation. This was facilitated by a welcome social event, interactive sessions, breaks and a delicious conference dinner! This edition of New Zealand Journal of Health and Safety Practice includes some of the abstracts from the conference programme. Please contact the listed authors if you would like to know more about their work and see hfesnz.org.nz to join the HFE conversations.